The solution of convolution-typed Volterra integral equation by G-transform - Kim, Hwajoon; Nonlaopon, Kamsing (International Journal of Engineering and Technology, 2019)
We would like to consider the solution of convolution-typed Volterra integral equation by using G-transform, a generalized Laplace-typed transform. The tool of G-transform is analyzed to be well applied to convolution-typed Volterra integral equation.